2017
DOI: 10.1155/2017/8728017
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Resistance and Its Association with Metabolic Syndrome in Korean Children

Abstract: Background This study investigated the association between insulin resistance (IR) and metabolic syndrome (MetS) in children. Methods A cross-sectional study involving 1036 healthy children aged between 7 and 13 years was conducted. Homeostasis model assessment of insulin resistance (HOMA-IR) was calculated as an index of IR. Participants were classified according to the HOMA-IR quartiles. Results Incremental, linear trends were found in age (p < 0.001), body mass index (BMI) (p < 0.001), body fat (p < 0.001),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 23 publications
2
21
0
2
Order By: Relevance
“…In other words, the presence of allele A is associated with a more significant deposit of fat, which is related to a higher number of cardio-metabolic complications [37]. This fact is explained by the increase in adipose tissue, which is associated with higher insulin resistance (IR) and represents the primary physiopathological mechanism of MetS [38]. Our results have shown that IR increases significantly between the different genotypes, being higher in AA (β = 1.010, p < 0.001) [25].…”
Section: Discussionmentioning
confidence: 99%
“…In other words, the presence of allele A is associated with a more significant deposit of fat, which is related to a higher number of cardio-metabolic complications [37]. This fact is explained by the increase in adipose tissue, which is associated with higher insulin resistance (IR) and represents the primary physiopathological mechanism of MetS [38]. Our results have shown that IR increases significantly between the different genotypes, being higher in AA (β = 1.010, p < 0.001) [25].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, abundant clinical and epidemiologic evidence has demonstrated a close linkage between IR and hypertension via enhanced salt absorption in the kidney, activation of the sympathetic nervous system, and alteration in vascular resistance (see reviewed [ 33 ]). Findings suggest that IR is significantly associated with the clustering of MetS risk factors [ 34 , 35 , 36 , 37 ], and IR is considered central to the pathophysiology of cardiometabolic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Considerando que el SM se caracteriza por presentar alteraciones en el metabolismo de los hidratos de carbono (aumento de glucosa >100 mg/dl) y los lípidos (triglicéridos >150 mg/dl, HDL < 40 mg/dl en hombres y < 50 mg/dl en mujeres), nuestro estudio mostró que los pacientes con SM+ presentan alteraciones metabólicas en comparación con los SM-. Este mismo comportamiento se ha observado en estudios previos [29][30][31] .…”
Section: Discussionunclassified